Assessment of different ionic adjustment strategies in low‐salinity water on the growth of Litopenaeus vannamei and microbial community stoichiometry in a synbiotic nursery system. (29th August 2021) - Pimentel, Otávio Augusto Lacerda Ferreira; de Oliveira, Valdemir Queiroz; Oliveira, Caio Rubens do Rêgo; Severi, William; Olivera Gálvez, Alfredo; Amado, André Megali; Brito, Luis Otavio
Abstract: The aim of this study was to evaluate different ionic adjustment strategies in oligohaline water on the growth of Litopenaeus vannamei and C:N:P stoichiometric ratios of the floc microbial community (MC) in synbiotic nursery system. A 35‐day culture (2000 PL's/m 3 ) was carried out in 60 L units in a completely randomized experimental design, with three treatments: T1—seawater diluted to a salinity of 2.5 g/L (control), T2—water with a salinity of 2.5 g/L with potassium (K⁺) adjusted and T3—water at a salinity of 2.5 g/L with its Ca:Mg:K ratio adjusted to 1:3:1, each treatment in triplicates. The MC of flocs and the dissolved fraction (DF) was separated by filtration, where MC >1.6 µm and DF <1.6 µm. The juveniles reached a final weight of 0.40 ± 0.09–0.49 ± 0.04 g, survival above 80% and an average yield of 0.69 ± 0.18–0.81 ± 0.02 kg/m 3, without significant differences among the treatments. A stabilizing trend of C:P, C:N and N:P ratios of MC was observed considering the variations of C:N:P in the DF, indicating a homeostatic behaviour of the floc MC, as occurs in systems with high nutrient availability. Our results indicate that the major ions initial concentrations (Ca 2+ : 25.07 mg/L, Mg 2+ : 89.75 mg/L and K⁺: 25.00 mg/L), total alkalinity 100.00 mg/L and total hardness 433.30 mg/L provide conditions that do not limit shrimp growth in oligohaline water synbiotic nursery system.